Dinâmica da curva de juros brasileira: uma análise da contribuição informacional de indicadores de incerteza na política econômica - Pedro Augusto Alvim Sabino (2022)
This thesis aim was to explain how the Brazilian yield curves dynamics is influenced by variations in American an Brazilian economic policy uncertainty. The sample used comprised monthly closings of the swap DI × Pre curve from B3, the Term Structure of Interest Rates estimated and provided by ANBIMA and the United States Term Structures of Interest Rates, uncertainty composite indicators (IIE-Br of Ferreira et al. (2019) and EPU of Baker, Bloom e Davis (2016)), in addition to macroeconomic variables, from February 2010 to June 2022. From this, the uncertainty indicators impacts were evaluated in regressions on the curve’s spreads, predictive regressions on excess returns, impulse response functions on the curve latent factors and, in particular, dynamic term strucutre models. In addition, also were evaluated the degree of integration between the swap curve and the ANBIMA curve and the spillover effects from American yield curve and uncertainty. The uncertainty indicators were significant to explaine the Brazilian curves spreads, but did not show predictive power over excess returns. Furthermore, the responses of the latent factors form the Brazilian curve to Brazilian uncertainty shocks were not significant, but, posteriorly, were slightly impacted by American uncertainty shocks, which propagated throughout the economic system. On the other hand, the likelihood ratio test reported significant fit gains in dynamic yield curve models when incorporating uncertainty proxies, especially the IIE-Br. This result suggests that, in the period evaluated, economic policy uncertainty did not show predictive power over the latent factors, which summarize the yield curve functional form in the following months. However, they also reinforce that it has an impact on bond pricing, improving the adjustment between expectations and risk premiums in no arbitrage models. As additional results, the usual implicit hypothesis of adherence between the swap curve and that of ANBIMA was corroborated. Also, it was found that the spillover from American uncertainty schocks on the Brazilian latent factors was significantly greater than that originated from Brazilian uncertainty, but the spillover form American uncertainty on the Brazilian was low.